Negative electrode composite material and preparation method thereof, battery and electronic device

By pre-oxidizing the biomass material and N-element doping coating of porous hard carbon materials, the problems of complex preparation process and insufficient electrochemical performance of existing sodium ion battery negative electrode materials are solved, and high reversible capacity and excellent electrochemical performance are achieved.

CN119812220AActive Publication Date: 2025-04-11JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411855392.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-11
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Existing sodium ion battery anode materials show complex preparation processes and inherent electrochemical defects in large-scale applications, resulting in serious shortcomings.

Method used

By pre-oxidizing the biomass material, porous hard carbon material is generated, and nitrogen-containing small molecule gas is evaporated during the decomposition process of nitrogen-containing polymer, the surface of the porous hard carbon material is doped and coated to form a nitrogen-doped hard carbon coating layer.

Benefits of technology

The effective filling and electrochemical performance of sodium ions are improved, the reversible capacity and cycle stability of the negative electrode material are enhanced, so that the sodium ion battery equipped with the negative electrode composite material has better electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812220A_ABST
    Figure CN119812220A_ABST
Patent Text Reader

Abstract

The invention relates to a negative electrode composite material and a preparation method thereof, a battery and an electronic device, and the preparation method comprises the following steps: carrying out pre-oxidation treatment on a biomass material to obtain a pre-oxidized biomass material; carrying out first calcination and acid pickling on the pre-oxidized biomass material in a mixed gas atmosphere, and carrying out second calcination in an inert gas atmosphere to obtain a porous hard carbon material; and in an inert gas atmosphere, placing a nitrogen-containing polymer and the obtained porous hard carbon material in different carriers of the same equipment, simultaneously performing third calcination, and cooling to obtain the negative electrode composite material. The sodium ion battery assembled with the negative electrode composite material has excellent first effect and cycle performance. The preparation method is simple and controllable, and can be suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a negative electrode composite material and a preparation method thereof, a battery and an electronic device. Background Art

[0002] Faced with increasingly severe environmental challenges and energy crises, people urgently need to develop renewable and sustainable energy sources, such as wind and solar energy. However, the effective conversion and utilization of these intermittent energy sources cannot be separated from the strong support of large-scale energy storage systems. In this context, sodium-ion batteries are regarded as the most promising alternative to lithium-ion batteries in large-scale energy storage due to their low cost, abundant sodium resource reserves, and a "rocking chair" working mechanism similar to lithium-ion batteries.

[0003] In the past decade, significant progress has been made in the research and application of cathode materials for sodium-ion batteries, including polyanionic compounds, layered oxides, and Prussian analogs. In terms of anode materials, a variety of materials such as carbonaceous materials, alloy metals, and metal chalcogenides have been widely explored. However, due to their complex preparation processes and inherent electrochemical defects, most candidate materials show serious deficiencies in large-scale applications.

[0004] Carbonaceous materials are considered the most promising negative electrode materials due to their low cost, simple preparation, and good reproducibility. Unlike the successful application of graphite in traditional lithium-ion batteries, the narrow carbon interlayer spacing (0.335nm) and thermodynamic instability of graphite embedded compounds hinder the embedding of sodium ions. Therefore, it is generally recognized that graphite cannot be directly used as a negative electrode material for sodium-ion batteries. In contrast, hard carbon is composed of interlaced graphite microcrystalline layers, abundant micropores and defects. It has a relatively large interlayer spacing, can store a large amount of sodium ions, and has a large reversible capacity.

[0005] Therefore, in order to meet the requirements of full batteries in practical applications, it is urgent to develop a hard carbon sodium-ion anode material with high reversible capacity and appropriate low-potential platform capacity. Summary of the invention

[0006] In view of this, embodiments of the present application provide a negative electrode composite material and a preparation method thereof, a battery, and an electronic device to solve at least one problem existing in the background technology.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] A first aspect of the present invention provides a method for preparing a negative electrode composite material, comprising the following steps:

[0009] S1: pre-oxidizing the biomass material to obtain a pre-oxidized biomass material;

[0010] S2: performing a first calcination on the pre-oxidized biomass material obtained in step S1 under a mixed gas atmosphere, acid washing, and performing a second calcination under an inert gas atmosphere to obtain a porous hard carbon material;

[0011] S3: Under an inert gas atmosphere, the nitrogen-containing polymer and the porous hard carbon material obtained in step S2 are placed in different carriers of the same device and simultaneously subjected to a third calcination, and the temperature is lowered to obtain the negative electrode composite material.

[0012] Preferably, in step S1, the biomass material is selected from one or more of cellulose, bamboo fiber, flax fiber, lignin, bagasse and straw;

[0013] Preferably, in step S1, the temperature of the pre-oxidation treatment is 200-350°C, the heating rate of the pre-oxidation treatment is 1-10°C / min, the holding time of the pre-oxidation treatment is 2-15 hours, and the pre-oxidation treatment is carried out in an air atmosphere.

[0014] Preferably, in step S2, the mixed gas is a mixed gas of hydrogen and an inert gas, the volume ratio of the hydrogen to the inert gas is 1:(14-24), and the inert gas is selected from at least one of argon, helium, and nitrogen;

[0015] Preferably, in step S2, the flow rate of the mixed gas is 50-100 ml / min, the temperature of the first calcination is 600-800°C, the heating rate of the first calcination is 1-10°C / min, and the holding time of the first calcination is 1-5 hours.

[0016] Preferably, in step S2, the pickling is pickling with stirring in a hydrochloric acid solution, the concentration of the hydrochloric acid solution is 0.5-1.5 mol / L, the stirring time is 8-16 hours, and the ratio of the mass (g) of the pre-oxidized biomass material to the volume (ml) of the hydrochloric acid solution is 1:(50-100);

[0017] Preferably, in step S2, after the pickling is completed, the steps of washing with deionized water until neutrality and drying are also included.

[0018] Preferably, in step S2, the inert gas is selected from at least one of argon, helium and nitrogen;

[0019] Preferably, the temperature of the second calcination is 1000-1600° C., the heating rate of the second calcination is 1-5° C. / min, and the holding time of the second calcination is 2-8 hours.

[0020] Preferably, in step S3, the distance between the carrier on which the nitrogen-containing polymer is placed and the inert gas inlet of the device is less than the distance between the carrier on which the porous hard carbon material is placed and the inert gas inlet of the device;

[0021] Preferably, in step S3, the mass ratio of the nitrogen-containing polymer to the porous hard carbon material is (3-5):1, and the nitrogen-containing polymer is selected from one or more of melamine resin, polyurethane resin, urea-formaldehyde resin, polysilazane resin, polyamide resin and ABS resin;

[0022] Preferably, in step S3, the inert gas is selected from at least one of argon, helium and nitrogen, the inert gas flow rate is 50-100 ml / min, the temperature of the third calcination is 400-800° C., the heating rate of the third calcination is 1-5° C. / min, and the holding time of the third calcination is 1-5 hours;

[0023] Preferably, in step S3, the cooling is firstly cooling to a first temperature at a first cooling rate, and then naturally cooling to room temperature, the first cooling rate is 1-10°C / min, and the first temperature is 400-600°C.

[0024] The second aspect of the present invention provides a negative electrode composite material, wherein the negative electrode composite material is prepared according to the preparation method of the negative electrode composite material provided by the first aspect of the present invention.

[0025] Among them, the negative electrode composite material includes the porous hard carbon material and a coating layer coated on the surface of the porous hard carbon material, the porous hard carbon material has a closed-pore structure, the coating layer is a nitrogen-doped hard carbon coating layer, the thickness of the coating layer is 3 to 10 nm, the closed-pore pore size of the negative electrode composite material is 0.8 to 2.0 nm, and the interlayer spacing of the negative electrode composite material is 0.37 to 0.385 nm.

[0026] Preferably, the atomic percentage of nitrogen atoms in the coating layer is 2 at% to 5 at%, and the C:O atomic ratio of the negative electrode composite material is (100 to 200): 1;

[0027] Preferably, the true density of the negative electrode composite material is 1.3 to 1.6 g / cm 3 The median particle size Dv50 of the negative electrode composite material is 2 to 10 μm, and the specific surface area of ​​the negative electrode composite material is 2 to 10 m 2 / g.

[0028] A third aspect of the present invention provides a battery, comprising a negative electrode plate, wherein the negative electrode plate comprises the negative electrode composite material provided by the second aspect of the present invention.

[0029] A fourth aspect of the present invention provides an electronic device, comprising the battery provided by the third aspect of the present invention.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The preparation method of the negative electrode composite material provided in the present application, firstly, pre-oxidation treatment is performed on the biomass material with a long molecular chain structure to increase the proportion of oxygen in the biomass material, which is conducive to making the hard carbon structure more disordered; then, the oxygen elements on the surface and bulk of the pre-oxidized biomass material are reduced by hydrogen, and the defect sites in the material are enriched. At the same time, the water molecules generated by hydrogen reduction can effectively form pores in the material, and a porous hard carbon material rich in closed pores is generated by high-temperature calcination, which is conducive to the effective filling of sodium ions; finally, the nitrogen-containing small molecule gas volatilized during the decomposition of the nitrogen-containing polymer is cleverly used to dope and coat the surface of the porous hard carbon material with N elements, effectively reducing the specific surface area of ​​the material and improving the interface stability, thereby forming a negative electrode composite material with a porous hard carbon material rich in closed pores inside and a nitrogen-doped hard carbon coating layer outside, which can effectively improve the first effect and cycle performance of the sodium ion battery equipped with the negative electrode composite material, so that it has more excellent electrochemical performance. In addition, the preparation method of the negative electrode composite material is simple and controllable, and can be applied to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0033] Figure 1 This is a SEM image of the nitrogen-doped hard carbon sodium ion battery negative electrode composite material obtained in Example 1.

[0034] Figure 2 This is the HRTEM image of the nitrogen-doped hard carbon sodium ion battery negative electrode composite material obtained in Example 1.

[0035] Figure 3 This is the XRD spectrum of the nitrogen-doped hard carbon sodium ion battery negative electrode composite material obtained in Example 1.

[0036] Figure 4 This is the SAXS graph of the nitrogen-doped hard carbon sodium ion battery negative electrode composite material obtained in Example 1, where the red line is the fitting line, and the flat part in the curve represents that the material has a closed-pore structure; the lower left corner of the figure is the closed-pore pore size. DETAILED DESCRIPTION

[0037] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is a detailed description by listing specific embodiments. Wherein, the drawings are not necessarily drawn to scale, and local features can be enlarged or reduced to more clearly show the details of local features. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually based on conventional experimental conditions. Reagents and raw materials used in the present invention are commercially available unless otherwise specified.

[0038] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.

[0039] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.

[0040] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.

[0041] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.

[0042] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.

[0043] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0044] [Preparation of negative electrode composite materials]

[0045] A first aspect of the present invention provides a method for preparing a negative electrode composite material, comprising the following steps:

[0046] S1: pre-oxidizing the biomass material to obtain a pre-oxidized biomass material;

[0047] S2: performing a first calcination on the pre-oxidized biomass material obtained in step S1 under a mixed gas atmosphere, acid washing, and performing a second calcination under an inert gas atmosphere to obtain a porous hard carbon material;

[0048] S3: Under an inert gas atmosphere, the nitrogen-containing polymer and the porous hard carbon material obtained in step S2 are placed in different carriers of the same device and simultaneously subjected to a third calcination, and the temperature is lowered to obtain the negative electrode composite material.

[0049] The preparation method provided in the present application first increases the proportion of oxygen in the biomass material by pre-oxidation treatment of the biomass material with a long molecular chain structure, which is beneficial to making the hard carbon structure more disordered; then, the oxygen elements on the surface and bulk of the pre-oxidized biomass material are reduced by hydrogen to enrich the defect sites in the material. At the same time, the water molecules produced by the hydrogen reduction can effectively form pores in the material, and a porous hard carbon material rich in closed pores is generated by high-temperature calcination, which is beneficial to the effective filling of sodium ions; finally, the nitrogen-containing small molecule gas volatilized during the decomposition of the nitrogen-containing polymer is cleverly utilized to dope and coat the surface of the porous hard carbon material with N elements, effectively reducing the specific surface area of ​​the material and improving the interface stability, thereby forming a negative electrode composite material with a porous hard carbon material rich in closed pores on the inside and a nitrogen-doped hard carbon coating layer on the outside, so that the sodium ion battery equipped with the negative electrode composite material has better electrochemical performance.

[0050] In certain embodiments, in step S1, the biomass material is selected from one or more of cellulose, bamboo fiber, flax fiber, lignin, bagasse and straw.

[0051] In certain embodiments, the biomass material is cellulose, bamboo fiber, flax fiber, or bagasse.

[0052] The above-mentioned biomass material has a long molecular chain structure, so it can form a rich network structure during the cross-linking reaction, and will form a richer closed-pore structure after carbonization, which is conducive to the effective filling of sodium ions, thereby significantly increasing the platform capacity, and thus making the sodium ion battery equipped with the negative electrode composite material have more excellent electrochemical performance.

[0053] In some embodiments, in step S1, the temperature of the pre-oxidation treatment is 200-350°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C or 350°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the heating rate of the pre-oxidation treatment is 1-10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, 20°C / min, 210°C / min, 220°C / min, 230°C / min, 240°C ℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min or 10℃ / min, but not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable; the holding time of the pre-oxidation treatment is 2 to 15 hours, for example 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours or 15 hours, but not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable; the pre-oxidation treatment is carried out in an air atmosphere.

[0054] In the present application, by pre-oxidation treatment of the biomass material and introduction of oxygen-containing functional groups by oxidative cross-linking, the proportion of oxygen in the biomass material can be increased, which can effectively optimize the hard carbon structure and make it more disordered; the platform capacity of the material can be effectively improved, thereby making the sodium ion battery equipped with the negative electrode composite material have better electrochemical performance.

[0055] In certain embodiments, in step S2, the mixed gas is a mixed gas of hydrogen and an inert gas, and the volume ratio of the hydrogen to the inert gas is 1:(14-24), for example, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23 or 1:24, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable, and the inert gas is selected from at least one of argon, helium, and nitrogen;

[0056] In some embodiments, in step S2, the mixed gas is a mixed gas of hydrogen and argon, and the volume ratio of hydrogen to argon is 1:(14-24), for example, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, 1:21, 1:22, 1:23 or 1:24, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In step S2 of the present invention, hydrogen is used to reduce oxygen elements on the surface and in the bulk of the pre-oxidized biomass material to enrich the defect sites of the material. At the same time, the water molecules generated by hydrogen reduction can effectively form pores in the material, thereby effectively improving the electrochemical performance of the sodium ion battery equipped with the negative electrode composite material.

[0058] In step S2 of the present invention, the reaction mechanism of using water molecules to form pores in the material is:

[0059] H 2 O+C x →H 2 +CO+C x-1

[0060] 2H 2 O+C→2H 2 +CO 2

[0061] In certain embodiments, in step S2, the flow rate of the mixed gas is 50 to 100 ml / min, for example, 50 ml / min, 60 ml / min, 70 ml / min, 80 ml / min, 90 ml / min or 100 ml / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0062] In certain embodiments, in step S2, the temperature of the first calcination is 600-800°C, for example, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C or 800°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the heating rate of the first calcination is The holding time of the first calcination is 1 to 5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0063] In certain embodiments, in step S2, the pickling is pickling with stirring in a hydrochloric acid solution, the concentration of the hydrochloric acid solution is 0.5-1.5 mol / L, for example, 0.5 mol / L, 1 mol / L or 1.5 mol / L, but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the stirring time is 8-16 hours, for example, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours, but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the ratio of the mass (g) of the pre-oxidized biomass material to the volume (ml) of the hydrochloric acid solution is 1:(50-100), for example, 1:50, 1:55, 1:60, 1:65, 1:70, 1:75, 1:80, 1:85, 1:90, 1:95 or 1:100, but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0064] In step S2 of the present application, pickling is beneficial to remove ash in the material, thereby facilitating the generation of more pores and the effective filling of sodium ions, thereby making the sodium ion battery equipped with the negative electrode composite material have better electrochemical performance.

[0065] In certain embodiments, in step S2, after the acid washing is completed, the steps of washing with deionized water until it becomes neutral and drying are also included.

[0066] In certain embodiments, in step S2, the inert gas is selected from at least one of argon, helium, and nitrogen.

[0067] In certain embodiments, in step S2, the inert gas is selected from argon.

[0068] In some embodiments, the temperature of the second calcination is 1000-1600°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C, but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable; the heating rate of the second calcination is 1-5°C / min, such as 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable; the holding time of the second calcination is 2-8 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable. Thus, the carbon atoms in the material can be rearranged at high temperature for graphitization, the carbon layer is bent, and nanopores are formed, which is conducive to the effective filling of sodium ions, so that the sodium ion battery equipped with the negative electrode composite material has better electrochemical performance.

[0069] In certain embodiments, in step S3, the distance between the carrier on which the nitrogen-containing polymer is placed and the inert gas inlet of the device is less than the distance between the carrier on which the porous hard carbon material is placed and the inert gas inlet of the device. Thus, the nitrogen-containing polymer can volatilize small molecule nitrogen gas during decomposition, which is deposited on the surface of the porous hard carbon material and plays a role of N element doping and coating, which can effectively reduce the specific surface area of ​​the material and improve the interface stability, thereby making the sodium ion battery equipped with the negative electrode composite material have more excellent electrochemical performance.

[0070] In certain embodiments, the apparatus is a tube furnace.

[0071] In certain embodiments, the carrier is a crucible.

[0072] In certain embodiments, in step S3, the mass ratio of the nitrogen-containing polymer to the porous hard carbon material is (3-5):1, for example, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable; the nitrogen-containing polymer is selected from one or more of melamine resin, polyurethane resin, urea-formaldehyde resin, polysilazane resin, polyamide resin and ABS resin.

[0073] In certain embodiments, the nitrogen-containing polymer is a melamine resin.

[0074] Since some micropores still exist in the form of open pores during the carbonization process, in order to avoid excessive side reactions in the first cycle due to the excessive specific surface area of ​​the material, the nitrogen-containing substances and short-chain molecular gases generated by the pyrolysis of the nitrogen-containing polymer are used to dope and coat the material with N elements. This can effectively reduce the specific surface area of ​​the material and improve the interface stability, thereby making the sodium ion battery equipped with the negative electrode composite material have better electrochemical performance.

[0075] In certain embodiments, in step S3, the inert gas is selected from at least one of argon, helium, and nitrogen; the inert gas flow rate is 50 to 100 ml / min, for example, 50 ml / min, 60 ml / min, 70 ml / min, 80 ml / min, 90 ml / min, or 100 ml / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the temperature of the third calcination is 400 to 800°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the heating rate of the third calcination is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable; the holding time of the third calcination is 1-5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0076] In certain embodiments, in step S3, the inert gas is selected from nitrogen.

[0077] In certain embodiments, in step S3, the cooling is first cooling to a first temperature at a first cooling rate, and then naturally cooling to room temperature; the first cooling rate is 1 to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable; the first temperature is 400 to 600°C, for example, 400°C, 450°C, 500°C, 550°C or 600°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0078] [Negative electrode composite material]

[0079] The second aspect of the present invention provides a negative electrode composite material, which is prepared according to the preparation method of the negative electrode composite material provided by the first aspect of the present invention, wherein the negative electrode composite material includes the porous hard carbon material and a coating layer coated on the surface of the porous hard carbon material, the porous hard carbon material has a closed-pore structure, and the coating layer is a nitrogen-doped hard carbon coating layer.

[0080] In some embodiments, the thickness of the coating layer is 3 to 10 nm, for example 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0081] In some embodiments, the closed-pore pore size of the negative electrode composite material is 0.8 to 2.0 nm, for example, 0.8 nm, 0.9 nm, 1.0 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm or 2.0 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0082] In certain embodiments, the interlayer spacing of the negative electrode composite material is 0.37-0.385 nm, such as 0.37 nm, 0.375 nm, 0.38 nm or 0.385 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0083] In some embodiments, the atomic percentage of nitrogen atoms in the coating layer is 2at% to 5at%, for example 2at%, 2.5at%, 3at%, 3.5at%, 4at%, 4.5at% or 5at%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] In some embodiments, the C:O atomic ratio of the negative electrode composite material is (100-200):1, for example 100:1, 110:1, 120:1, 130:1, 140:1, 150:1, 160:1, 170:1, 180:1, 190:1 or 200:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0085] In some embodiments, the true density of the negative electrode composite material is 1.3 to 1.6 g / cm 3 , for example 1.3 g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 or 1.6 g / cm 3 , but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0086] In some embodiments, the median particle size Dv50 of the negative electrode composite material is 2 to 10 μm, for example 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0087] In some embodiments, the specific surface area of ​​the negative electrode composite material is 2 to 10 m 2 / g. For example, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g or 10m 2 / g, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0088] It should be understood that since the negative electrode composite material provided in the present application is prepared according to the preparation method of the negative electrode composite material provided in the first aspect of the present invention, the beneficial effects of the preparation method of the negative electrode composite material described in any of the above embodiments are applicable to the negative electrode composite material.

[0089] [Battery]

[0090] A third aspect of the present invention provides a battery, comprising a negative electrode plate, wherein the negative electrode plate comprises the negative electrode composite material provided by the second aspect of the present invention.

[0091] In some embodiments, the battery may be a secondary battery or a primary battery, preferably a secondary battery. For example, the battery may be a sodium ion battery, etc., but is not limited thereto. The battery structure of the present application includes but is not limited to a soft-pack sodium ion battery, a square hard-shell battery, or a cylindrical hard-shell battery, etc.

[0092] The battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is arranged between the positive electrode sheet and the negative electrode sheet. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly playing a role in preventing the positive / negative electrode from short-circuiting, and at the same time allowing ions to pass through.

[0093] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode current collector can be aluminum foil, copper foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The negative electrode active material layer includes a negative electrode active material. In the present invention, the negative electrode active material is the negative electrode composite material provided in the second aspect of the present invention.

[0094] The negative electrode active material layer may also include one or two selected from a conductive agent and a binder. The conductive agent is used to improve the conductivity of the electrode. Examples of negative electrode conductive agents include conductive carbon black, conductive graphite, vapor deposited carbon fiber (VGCF), carbon nanotubes, graphene, etc. The binder of the negative electrode improves the bonding performance between the negative electrode active material particles and between the negative electrode active material particles and the current collector. Examples of negative electrode binders include polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), cyclodextrin, gelatin, polyvinyl alcohol, polyacrylate, acrylonitrile multipolymer, etc. The mass ratio of each component in the negative electrode active material layer can be conventional.

[0095] The present application has no particular restrictions on the preparation method of the negative electrode sheet, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the negative electrode sheet includes but is not limited to the following steps: dispersing the negative electrode active material, the conductive agent, and the binder in a solvent and mixing them to form a uniform negative electrode slurry, coating the negative electrode slurry on the negative electrode collector, and obtaining the negative electrode sheet after drying, cold pressing, cutting, slitting and re-drying. The solvent of the negative electrode slurry can be a conventional solvent in the art, such as deionized water.

[0096] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode current collector may be aluminum foil, copper foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material suitable for the present invention may be various known positive electrode active materials that can be used for sodium ion batteries, which can reversibly embed and de-embed sodium ions. The positive electrode active material may be a sodium ion positive electrode active material commonly used in the art, preferably selected from sodium iron composite oxides (such as NaFeO 2 ), sodium cobalt composite oxides (such as NaCoO 2 ), sodium chromium composite oxide (such as NaCrO 2 ), sodium manganese composite oxides (such as NaMnO 2 ), sodium nickel composite oxides (such as NaNiO 2 ), sodium nickel titanium composite oxide (such as NaNi0 .5 Ti 0.5 O 2 ), sodium nickel manganese composite oxides (such as NaNi 0.5 Mn 0.5 O 2 ), sodium iron manganese composite oxide (such as Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O 2 ), sodium nickel cobalt manganese composite oxides (such as NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 ), sodium iron phosphate compounds (such as NaFePO 4 ), sodium manganese phosphate compounds (such as NaMnPO 4 ) and sodium cobalt phosphate compounds (such as NaCoPO 4 )

[0097] The positive electrode active material layer may also include one or two selected from a conductive agent and a binder. The conductive agent is used to improve the conductivity of the electrode. Examples of the conductive agent of the positive electrode include one or more of conductive carbon black, carbon fiber (CF), acetylene black, Ketjen black, graphene, carbon nanotubes and carbon microspheres. The binder of the positive electrode improves the bonding performance between the positive electrode active material particles and between the positive electrode active material particles and the current collector. Examples of the binder of the positive electrode include at least one of a fluorine-containing resin, a polypropylene resin, a fiber-type binder, a rubber-type binder and a polyimide-type binder. The mass ratio of each component in the positive electrode active material layer can be conventional.

[0098] The present application has no particular restrictions on the preparation method of the positive electrode sheet, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet includes but is not limited to the following steps: dispersing the positive electrode active material, the conductive agent, and the binder in a solvent and mixing them to form a uniform positive electrode slurry, coating the positive electrode slurry on the positive electrode collector, and obtaining the positive electrode sheet after drying, cold pressing, cutting, slitting and re-drying. The solvent of the positive electrode slurry can be a conventional solvent in the art, such as N-methylpyrrolidone (NMP).

[0099] The separator can be a polymer porous separator, an inorganic porous separator or a polymer-inorganic composite porous separator. The polymer porous separator includes a single-layer polymer porous separator and a multi-layer polymer porous separator.

[0100] The electrolyte generally comprises a solvent and a sodium salt. The electrolyte suitable for the present invention may be conventional, for example, the solvent may be one or more selected from dimethyl carbonate (DMC), propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) or 1,4-butyl propyl ester, more preferably one or more of PC, EC and EMC. The sodium salt may be one or more selected from sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoromethanesulfonate or sodium perchlorate.

[0101] The battery of the present application also includes a packaging shell for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in a sodium ion battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging shell, and it can be a packaging shell known in the art, as long as it can achieve the purpose of the present application.

[0102] [Electronic devices]

[0103] The fourth aspect of the present invention provides an electronic device, the electronic device comprising the battery provided by the third aspect of the present invention

[0104] The use of the battery of the present application is not particularly limited, and it can be used in any electronic device known in the prior art. In some embodiments, the battery of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, drones, and sodium ion capacitors, etc.

[0105] It should be understood that, since the electronic device provided in the present application includes the battery described in the third aspect of the present invention, the beneficial effects of the method for preparing the negative electrode material described in any of the above embodiments are applicable to the electronic device.

[0106] The method of the present invention is described below by means of specific examples. It should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions adopted in the examples can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in routine experiments.

[0107] Example 1

[0108] S101: 50 g of cellulose (i.e., biomass material) is placed in a crucible and placed in a tube furnace. In an air atmosphere, the temperature is raised from 25 degrees Celsius to 260 degrees Celsius at a rate of 2 degrees per minute and kept for 10 hours to perform a pre-oxidation process to obtain a pre-oxidized biomass material;

[0109] S102: 30 g of pre-oxidized biomass material was placed in a tube furnace under H 2 / Ar mixed gas atmosphere (where H 2 The ratio of the mixed gas is 5%), the temperature is increased from 25 degrees Celsius to 700 degrees Celsius at a heating rate of 2 degrees per minute, and the temperature is kept for 2 hours for calcination. After the calcination, it is placed in 2.4L of 1mol / L hydrochloric acid solution for stirring and pickling for 12 hours. After the pickling is completed, it is washed with deionized water to neutrality and dried. Subsequently, the pickled material is placed in a crucible, and in an argon atmosphere, the temperature is increased to 1300 degrees Celsius at a heating rate of 2 degrees per minute, and the temperature is kept for 5 hours to obtain a porous hard carbon material.

[0110] S103: Put 20g of nitrogen-containing polymer (melamine resin) and 5g of porous hard carbon material into two side-by-side crucibles respectively, and place them in a tubular furnace. The crucible containing the nitrogen-containing polymer is placed close to the air inlet of the tubular furnace. In a nitrogen atmosphere, the temperature is increased from 25 degrees Celsius to 600 degrees Celsius at a heating rate of 2 degrees per minute, and the temperature is kept for 2 hours for calcination. Then, the temperature is first reduced to 500 degrees at a cooling rate of 5 degrees per minute, and then naturally cooled to room temperature to obtain a high-performance nitrogen-doped hard carbon sodium ion battery negative electrode material.

[0111] Example 2

[0112] The only difference between Example 2 and Example 1 is that the cellulose in step S101 of Example 1 is replaced by bamboo fiber.

[0113] Example 3

[0114] The only difference between Example 3 and Example 1 is that the cellulose in step S101 of Example 1 is replaced by flax fiber.

[0115] Example 4

[0116] The only difference between Example 4 and Example 1 is that the cellulose in step S101 of Example 1 is replaced by bagasse.

[0117] Comparative Example 1

[0118] 50 g of cellulose was placed in a crucible and placed in a tubular furnace. Under a nitrogen atmosphere, the temperature was raised from 25 degrees Celsius to 1300 degrees Celsius at a rate of 2 degrees per minute and kept warm for 10 hours to obtain a negative electrode material for a sodium ion battery.

[0119] Comparative Example 2

[0120] The only difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not include step S103 in Example 1, and the porous hard carbon material is prepared only by steps S101 and S102 in Example 1.

[0121] Comparative Example 3

[0122] Step S101*: 50 g of cellulose (i.e., biomass material) is placed in a crucible and placed in a tube furnace. Under a nitrogen atmosphere, the temperature is raised from 25 degrees Celsius to 1300 degrees Celsius at a heating rate of 2 degrees per minute and kept for 10 hours for calcination. After the calcination is completed, a pyrolyzed biomass material is obtained;

[0123] Step S102*: The nitrogen-containing polymer and the pyrolyzed biomass material are placed in two side-by-side crucibles respectively. The crucible containing the nitrogen-containing polymer is placed near the air inlet. In a nitrogen atmosphere, the temperature is increased from 25 degrees Celsius to 600 degrees Celsius at a heating rate of 2 degrees per minute, and the temperature is kept for 2 hours for calcination. Subsequently, the temperature is first reduced to 500 degrees at a cooling rate of 5 degrees per minute, and then naturally cooled to room temperature to obtain a negative electrode material for a sodium ion battery.

[0124] Electrochemical performance test

[0125] Sodium ion battery preparation:

[0126] (1) Preparation of negative electrode sheet: The negative electrode materials prepared in the above Examples 1 to 4 and Comparative Examples 1 to 3 are used as negative electrode active materials, carbon black is used as a conductive agent, and CMC is used as a binder. The mixture is mixed in a ratio of negative electrode active material: conductive agent: binder = 8:1:1, and the mixture is evenly coated on a negative electrode current collector (Cu foil) on a transfer coater, and then rolled and sliced ​​to form a negative electrode sheet;

[0127] (2) Preparation of positive electrode sheet: using a metal sodium sheet as the positive electrode sheet;

[0128] (3) Diaphragm: Glass fiber diaphragm is used as the diaphragm;

[0129] (4) Electrolyte: The electrolyte is 1.0 mol / L NaPF 6 Prepared by dissolving in diethylene glycol dimethyl ether;

[0130] (5) Battery assembly: The negative electrode sheet, the separator, and the positive electrode sheet were assembled in order and soaked in electrolyte respectively to form a CR2032 button battery in an argon glove box.

[0131] The performance of CR2032 button batteries using the negative electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 as negative electrode active materials was tested.

[0132] 1. First discharge capacity, first charge capacity and first coulomb efficiency test: Use Land battery test system to perform discharge and charge test at 0.1C / 0.1C rate at 25℃, with voltage range of 0~2V. Specifically: discharge at 0.1C rate to 0V, record the discharge capacity at this time as the first discharge capacity; then charge at 0.1C rate to 2V, record the charge capacity at this time as the first charge capacity; first coulomb efficiency = first charge capacity / first discharge capacity*100%. The test results are shown in Table 1.

[0133] Table 1

[0134] Example First discharge capacity mAh / g First charge capacity mAh / g First coulombic efficiency (%) Example 1 448.3 408.4 91.1 Example 2 449.1 407.8 90.8 Example 3 448.5 407.7 90.9 Example 4 447.6 408.2 91.2 Comparative Example 1 319.3 265.3 83.1 Comparative Example 2 388.4 293.6 75.6 Comparative Example 3 375.4 320.2 85.3

[0135] The button-type half-cells using the negative electrode composite materials prepared in Examples 1 to 4 of the present application as negative electrode active materials all have a high initial discharge capacity (all exceeding 400 mAh / g) and the first storage efficiency exceeds 90%. Compared with Example 1, Comparative Example 1 does not pre-oxidize cellulose, but directly pyrolyzes and carbonizes to obtain the negative electrode material; Comparative Example 2 does not include the nitrogen coating step; Comparative Example 3 directly pyrolyzes cellulose and then nitrogen coats it, so the first discharge capacity of Comparative Examples 1 to 3 is only 265.3 to 320.2 mAh / g, and the first coulomb efficiency is 75.6% to 85.3%. This is because after pre-oxidation and cross-linking, the biomass material can form more defects by removing oxygen atoms, and the carbon atoms are rearranged at high temperature to generate more closed pores. At the same time, nitrogen doping also provides adsorption capacity, which is conducive to providing more storage space for sodium ions; in addition, the interface structure of the nitrogen-doped material is conducive to the formation of a compact SEI layer, thereby effectively improving the first coulomb efficiency.

[0136] 2. Capacity retention rate test: Use the Blue Battery Test System, at 25°C, discharge to 0V at 1C constant current, then charge to 2V at 1C constant current, record the charging capacity at this time as the first cycle charging capacity, this is one cycle; repeat this process for 500 cycles, record the charging capacity of the 500th cycle, capacity retention rate = 500th cycle charging capacity / first cycle charging capacity * 100%. The test results are shown in Table 2.

[0137] Table 2

[0138] Example Capacity retention rate (%) Example 1 92.8 Example 2 93.2 Example 3 93.3 Example 4 93.6 Comparative Example 1 82.8 Comparative Example 2 80.7 Comparative Example 3 87.3

[0139] The button-type half-cells using the negative electrode composite materials prepared in Examples 1 to 4 of the present application as the negative electrode active material all have a high capacity retention rate after 500 cycles (all greater than 92%). Compared with Example 1, the capacity retention rates of Comparative Examples 1 to 3 are only 82.8% to 87.3%. This shows that the negative electrode material prepared by the preparation method of the present application can provide a continuous conductive framework due to its rich microporous structure, which can shorten the transmission distance during ion and electron transmission. At the same time, the good mechanical properties and stable interface are conducive to the formation of a dense SEI layer, so that the battery has good cycle stability, thereby improving the overall electrochemical performance of the electrode.

[0140] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.

Claims

1. A method for preparing a negative electrode composite material, characterized in that: The following steps are involved: S1: pre-oxidizing the biomass material to obtain a pre-oxidized biomass material; S2: performing a first calcination on the pre-oxidized biomass material obtained in step S1 under a mixed gas atmosphere, acid washing, and performing a second calcination under an inert gas atmosphere to obtain a porous hard carbon material; S3: Under an inert gas atmosphere, the nitrogen-containing polymer and the porous hard carbon material obtained in step S2 are placed in different carriers of the same device and simultaneously subjected to a third calcination, and the temperature is lowered to obtain the negative electrode composite material.

2. The method for preparing the negative electrode composite material according to claim 1, characterized in that: In step S1, the biomass material is selected from one or more of cellulose, bamboo fiber, flax fiber, lignin, bagasse and straw; In step S1, the temperature of the pre-oxidation treatment is 200-350°C, the heating rate of the pre-oxidation treatment is 1-10°C / min, the holding time of the pre-oxidation treatment is 2-15 hours, and the pre-oxidation treatment is performed in an air atmosphere.

3. The method for preparing the negative electrode composite material according to claim 1, characterized in that: In step S2, the mixed gas is a mixed gas of hydrogen and an inert gas, the volume ratio of the hydrogen to the inert gas is 1:(14-24), and the inert gas is selected from at least one of argon, helium, and nitrogen; Preferably, in step S2, the flow rate of the mixed gas is 50-100 ml / min, the temperature of the first calcination is 600-800°C, the heating rate of the first calcination is 1-10°C / min, and the holding time of the first calcination is 1-5 hours.

4. The method for preparing the negative electrode composite material according to claim 1, characterized in that: In step S2, the pickling is pickling with stirring in a hydrochloric acid solution, the concentration of the hydrochloric acid solution is 0.5-1.5 mol / L, the stirring time is 8-16 hours, and the ratio of the mass (g) of the pre-oxidized biomass material to the volume (ml) of the hydrochloric acid solution is 1:(50-100); Preferably, in step S2, after the pickling is completed, the steps of washing with deionized water until neutrality and drying are also included.

5. The method for preparing the negative electrode composite material according to claim 1, characterized in that: In step S2, the inert gas is selected from at least one of argon, helium and nitrogen, the temperature of the second calcination is 1000-1600°C, the heating rate of the second calcination is 1-5°C / min, and the insulation time of the second calcination is 2-8 hours.

6. The method for preparing the negative electrode composite material according to claim 1, characterized in that: In step S3, the distance between the carrier on which the nitrogen-containing polymer is placed and the inert gas inlet of the device is less than the distance between the carrier on which the porous hard carbon material is placed and the inert gas inlet of the device; Preferably, in step S3, the mass ratio of the nitrogen-containing polymer to the porous hard carbon material is (3-5):1, and the nitrogen-containing polymer is selected from one or more of melamine resin, polyurethane resin, urea-formaldehyde resin, polysilazane resin, polyamide resin and ABS resin; Preferably, in step S3, the inert gas is selected from at least one of argon, helium and nitrogen, the inert gas flow rate is 50-100 ml / min, the temperature of the third calcination is 400-800° C., the heating rate of the third calcination is 1-5° C. / min, and the holding time of the third calcination is 1-5 hours; Preferably, in step S3, the cooling is firstly cooling to a first temperature at a first cooling rate, and then naturally cooling to room temperature, the first cooling rate is 1-10°C / min, and the first temperature is 400-600°C.

7. A negative electrode composite material, characterized in that: The negative electrode composite material is prepared according to the method for preparing a negative electrode composite material according to any one of claims 1 to 6, Among them, the negative electrode composite material includes the porous hard carbon material and a coating layer coated on the surface of the porous hard carbon material, the porous hard carbon material has a closed-pore structure, the coating layer is a nitrogen-doped hard carbon coating layer, the thickness of the coating layer is 3 to 10 nm, the closed-pore pore size of the negative electrode composite material is 0.8 to 2.0 nm, and the interlayer spacing of the negative electrode composite material is 0.37 to 0.385 nm.

8. The negative electrode composite material according to claim 7, characterized in that: The atomic percentage of nitrogen atoms in the coating layer is 2 at% to 5 at%, and the C:O atomic ratio of the negative electrode composite material is (100 to 200):1; Preferably, the true density of the negative electrode composite material is 1.3 to 1.6 g / cm 3 The median particle size Dv50 of the negative electrode composite material is 2 to 10 μm, and the specific surface area of ​​the negative electrode composite material is 2 to 10 m 2 / g.

9. A battery, characterized in that: The battery comprises a negative electrode plate, and the negative electrode plate comprises the negative electrode composite material as claimed in claim 7 or 8.

10. An electronic device, characterized in that: The electronic device comprises the battery as claimed in claim 9.

Citation Information

Patent Citations

  • Nitrogen-doped reduced graphene oxide modified graphite felt electrode and preparation method thereof

    CN108598498A

  • Sodium ion battery with high power characteristic

    CN114373929A

  • Bacterial cellulose / resin composite material as well as preparation method and application thereof

    CN116855035A

  • Biomass carbon material as well as preparation method and application thereof

    CN117185288A

  • Biomass hard carbon negative electrode material and preparation method and application thereof

    CN117208886A